2016
DOI: 10.1111/apps.12080
|View full text |Cite
|
Sign up to set email alerts
|

Rewards and Creativity: Past, Present, and Future

Abstract: Research on the effects of rewards on creativity has resulted in hundreds of empirical studies and several reviews of the reward-creativity relationship (RCR). Most reviews are retrospective in nature. They have quantitatively summarised and integrated previous research findings, but have largely overlooked the need for a theoretical framework to guide future research. The current systematic review of this literature intends to bridge this gap, based on the findings of 329 papers and book chapters. Our review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 112 publications
(163 reference statements)
1
44
0
2
Order By: Relevance
“…Despite the intensity of this research stream, creativity researchers must continue resolving several unsettled issues. A recent issue relates to the classification of different types of creativity and the identification of antecedents and boundary conditions of each creativity type (Malik & Butt, ). Another issue concerns the importance of intrinsic motivation versus extrinsic rewards in promoting creativity (Gerhart & Fang, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the intensity of this research stream, creativity researchers must continue resolving several unsettled issues. A recent issue relates to the classification of different types of creativity and the identification of antecedents and boundary conditions of each creativity type (Malik & Butt, ). Another issue concerns the importance of intrinsic motivation versus extrinsic rewards in promoting creativity (Gerhart & Fang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Expanding prior research exploring the motivational processes of different types of creativity (Gilson et al, ; Gilson & Madjar, ), we specify the motivational processes underlying the radical and incremental creativity of employees. Research on the effects of intrinsic and extrinsic rewards on creativity has a long history filled with controversies (Cerasoli, Nicklin, & Ford, ; Malik & Butt, ), and the role of extrinsic rewards remained at the center of this debate because of inconsistent and mixed findings (Shalley et al, ). In the meta‐analysis of Byron and Khazanchi (), they concluded that extrinsic rewards associated with generalized performance may harm creativity, whereas extrinsic rewards offered for creativity have an overall positive effect on creativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu (2011) agreed with this research in brand loyalty as a significant positive influence on hospital brand image, improving patient satisfaction through enhancing the perception of service quality, which in turn increases the re-visit intention of patients. Malik et al (2012) focus on how significant is the relation between (brand knowledge, brand social responsibility image, service involvement and perceived service quality) and brand loyalty. And this confirms the strong relation between these dimensions together.…”
Section: Research Discussionmentioning
confidence: 99%
“…Finally, perceived quality was significant in this study, as agreed by Chahal and Bala (2010), who found that perceived quality has an influence on brand equity as a component. Malik et al (2012) focused on the significant relation between perceived quality and brand loyalty. Moreover, it can be concluded from that study that the presumptive order of the components of brand equity are perceived quality, brand loyalty, brand awareness and brand image.…”
Section: Research Discussionmentioning
confidence: 99%